Enteral electrolytic solutions administered in continuous flow via naso-ruminal route in adult goats - SANTOS, Paulo Vinicius de M. (J Vet Med Sci, 2020)
This study aimed to investigate the effects of maintenance enteral electrolytic solutions administered naso-ruminally in continuous flow in adult goats subjected to water and food restriction. Six adult non-pregnant and non-lactating female goats, aged between two and five years old, were used in a crossover (6 × 2) study. Solution 1 (SEE1) comprised: 4.5 g sodium chloride (NaCl); 1 g potassium chloride (KCl); 0.5 g magnesium chloride (MgCl); 1 g calcium chloride in 1,000 ml of water (measured osmolarity: 202 mOsm/l). Solution 2 (SEE2) comprised: 4.5 g of NaCl; 1 g of KCl; 0.5 g of MgCl; 2 g of calcium acetate in 1,000 ml of water (measured osmolarity: 212 mOsm/l). The solutions were administered naso-ruminally at a dose rate of 15 ml/kg/hr, for 12 hr. The animals were evaluated at times T-24, T0, T4, T8, T12, and T24. Both enteral electrolytic solutions were effective in expanding blood volume. SEE1 showed a low-intensity acidifying potential, while SEE2 showed behavior of a neutral enteral electrolytic solution.